Evaluasi Formulasi Kebijakan Anggaran Pendapatan dan Belanja Daerah Kabupaten Sumba Barat - Lebu Gallu; Susanti Susanti; Leo Agustino (Mahesa Research Center, 2023)
This article aims to evaluate the formulation of the Regional Revenue and Expenditure Budget (APBD) in West Sumba Regency, specifically during the fiscal year 2019/2020. The research focuses on the stages of APBD formulation, namely the drafting of APBD, the formulation of the General Budget Policy (KUA), the formulation of the Temporary Budget Ceiling (PPAS), the preparation of Regional Working Plans and Budgets of Regional Apparatus (RKA-SKPD), the verification of RKA-SKPD, and the enactment of the Regional Regulation on the APBD (Ranperda APBD). The qualitative method with a descriptive approach is used in this study. Data was collected through interviews and document studies. The Miles and Huberman data analysis method was employed. The findings indicate that, overall, the APBD formulation process adhered to the applicable legal provisions. However, several shortcomings were identified. Firstly, there were delays in the evaluation of the formulation. Secondly, many of the aspirations of the West Sumba community were not accommodated in the KUA during the APBD formulation. Thirdly, inconsistencies between Regional Medium-Term Development Plans (RKPD) and RKA SKPD were due to inadequate socialization during the preparation of RKA-SKPD. Fourthly, RKA-SKPD verification was hurried, impacting the effectiveness of the verification process. Finally, the West Sumba APBD Ranperda should have been socialized to the public before being ratified by the Regional People's Representative Council (DPRD), which was not carried out. These findings highlight the limited involvement of actors in the formulation of the West Sumba APBD due to the dominant role of the government in the formulation process. This contrasts with the policy network theory, which emphasizes the significance of involving various actors in decision-making to enhance the quality of decisions taken.